Resonance Raman and UV‐Visible Microscopy Reveals that Conditioning Red Blood Cells with Repeated Doses of Sodium Dithionite Increases Haemoglobin Oxygen Uptake. Issue 11 (19th April 2017) - Perez–Guaita, David; de Veij, Marleen; Marzec, Katarzyna M.; Almohammedi, Abdullah R. D.; McNaughton, Don; Hudson, Andrew J.; Wood, Bayden R.
Abstract: Here we report that successive additions of fresh dithionite to a suspension of red blood cells (RBCs) increase the capacity of the cells to uptake oxygen. This effect was not observed when the RBCs were similarly preconditioned using gaseous N2 to induce short episodes of hypoxia. The effect of successive sodium dithionite and N2 gas additions on a population of functional erythrocytes was monitored using Raman confocal microscopy, with 514 nm excitation, and UV–visible microscopy. The results indicate that successive additions of sodium dithionite in a suspension of red blood cells leads to an increase in both the rate and the capacity of the RBCs to uptake oxygen. The sodium dithionite did not cause haemoglobin from lysed RBCs to uptake more oxygen after successive additions and hence this effect was only observed in functional intact RBCs. Experiments performed with polarised Raman spectroscopy suggest that sodium dithionite increases the disorder of Hb in the RBC facilitating oxygen diffusion. Abstract : Using a combination of laser tweezer Raman microscopy, UV/Vis microscopy and conventional Raman polarised microscopy we show that successive conditioning of erythrocytes with sodium dithionite increases the uptake and overall concentration of oxygen within the red blood cell. Experiments performed using polarised Raman spectroscopy suggest that sodium dithionite increases the disorder of haemoglobin in the RBC thus facilitating oxygen diffusion within the haemoglobin matrix.